Fuel mixtures of oil sludge and waste oils: comprehensive ignition and combustion analysis; Energy Conversion and Management; Vol. 348, Pt. B - Vershinina K. Yu. Kseniya Yurievna; Dorokhov V. V. Vadim Valerjevich; Kartashova K. A. Kseniya Andreevna; Kovtunets I. S. Igor Stanislavovich; Strizhak P. A. Pavel Alexandrovich (2026, 2026)
Title screen